Gambaran Kepuasan Pelayanan Dan Kepuasan Pasien Hemodialisa Di Rumah Sakit X - Aussi Dwifungsiania (Universitas Ibn Khaldun Bogor, 2021)
Service to satisfy customers does not have to be at the expense of self-esteem or self-image because providing services is not based on the submission of one party to another, the service should be carried out to realize the best benefits for all parties. The purpose of this study was to describe the quality of services provided by the hemodialysis unit to outpatients and the satisfaction of hemodialysis patients during dialysis at hospital X. The research method used was quantitative, by distributing questionnaires to the patient's guardians. The results of the study, the results showed, 100% of respondents in the HD unit of Hospital X said it was true about the quality of services contained in the HD unit of Hospital X. The results showed, 100% said they were satisfied with the services provided by the HD unit of Hospital X. Maintained service well in the eyes of hemodialysis patients at X Hospital.